2018
DOI: 10.1038/s41598-018-34649-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the capsular GalXM-induced IL-17 cytokine in the control of Cryptococcus neoformans infection

Abstract: Cryptococcus neoformans is an opportunistic fungus that can cause lethal brain infections in immunosuppressed individuals. Infection usually occurs via the inhalation of a spore or desiccated yeast which can then disseminate from the lung to the brain and other tissues. Dissemination and disease is largely influence by the production of copious amounts of cryptococcal polysaccharides, both which are secreted to the extracellular environment or assembled into a thick capsule surrounding the cell body. There are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 113 publications
(117 reference statements)
1
21
0
Order By: Relevance
“…In order to fully understand the effect of K. pneumoniae LPS O2afg-antigen in modulating immune responses through NF-κB, these factors must also be considered and future studies will unravel their role in this immune evasion mechanism. When monocytes’ stimulation is performed with the LPS O2afg-antigen (either from 6613 or ST258), PMB seems to restore the levels of pro-inflammatory molecules ( Figure 3 B,C,E), which suggests that PMB could not only act as a negative immune-modulator of inflammatory response, but, at an early stage, it could revert immune evasion as previously demonstrated for other bacterial LPS [ 47 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 72%
“…In order to fully understand the effect of K. pneumoniae LPS O2afg-antigen in modulating immune responses through NF-κB, these factors must also be considered and future studies will unravel their role in this immune evasion mechanism. When monocytes’ stimulation is performed with the LPS O2afg-antigen (either from 6613 or ST258), PMB seems to restore the levels of pro-inflammatory molecules ( Figure 3 B,C,E), which suggests that PMB could not only act as a negative immune-modulator of inflammatory response, but, at an early stage, it could revert immune evasion as previously demonstrated for other bacterial LPS [ 47 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 72%
“…Similar to IFN-γ, IL-17 appears to play an important role in controlling infection by Cryptococcus spp. In a model of infection by C. neoformans (B3501 strain) in C57BL/6 IL-17-deficient mice, the role of this cytokine in controlling the disease was identified 35 , mainly due to the activity modulator of GXM. It has also been described www.nature.com/scientificreports/ that, in a model of infection by C. neoformans, a greater infiltration of Th17 lymphocytes was observed in the lungs of C57BL/6 mice, as well as an increased amount of IL-17 in this tissue 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the importance of the Th17 response in the control of fungal infections, especially in opportunistic fungal models such as C. neoformans, C. albicans and A. fumigatus 35,37,50,51 . IL-17A is important for total lung leukocyte recruitment and accumulation 14 days after infection by C. neoformans, as well as the reduction of inflammation and increase in fungal load 50 .…”
Section: Tlr9 −/− Mice Have Higher Fungal Load In the Brain And Spleementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that treatment with GalXM activates dendritic cells and induces Th17 differentiation when co-cultured with T cells. The authors also demonstrated that treating mice with GalXM prior to infection induced immune protection and this phenomenon was dependent on IL-6 and IL-17 production (108).…”
Section: Immunomodulatory Activity Of Galxmmentioning
confidence: 99%